Profil Vitiligo Anak Pasien Rawat Jalan Poliklinik Dermatologi dan Venereologi Rumah Sakit Umum Dr. Moewardi Surakarta - Ivani, Ivani; Mulianto, Nur M Rachmat; Hidayati, Nurul (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Vitiligo is the most common skin depigmentation condition that occurs in society, around 0.5% -2% of the entire population in the world. Vitiligo occurs as a result of selective and progressive loss of melanocytes in the skin which results in a white macule that is not scaly. To know the profile of vitiligo patients in General Hospital Dr. Moewardi Surakarta in order to achieve proper management. The study was conducted retrospectively by looking at the medical records of vitiligo patients at the Dermatology and Venereology Polyclinic of the Hospital. Moewardi Surakarta for the period January 2019 to December 2022. There were 42 patients with vitiligo in children within 3 years with the highest age range being 13 years. Based on gender characteristics, the number of pediatric vitiligo patients was not much different between men and women, in men there were 17 people (40.48%) and in women there were 25 people (59.52%). With the most lesion areas on the face as many as 25 people. The most widely given therapy was phototherapy with a distribution of 14 people (33%) who received this therapy. 42 vitiligo patients who went to the Dermatology and Venereology Polyclinic at General Hospital Dr. Moewardi Surakarta in the period from January 2019 to December 2022. Vitiligo in children is more common in women with the largest age group being 13 years old. Vitiligo lesions most often appear on the face. Most therapy in patients with phototherapy. Keywords: Vitiligo, Phototherapy, Pigmentation Disorder  ABSTRAK Vitiligo merupakan kondisi depigmentasi kulit yang paling umum terjadi di masyarakat, sekitar 0,5%-2% dari seluruh populasi di dunia. Vitiligo terjadi akibatnya hilangnya melanosit pada kulit secara selektif dan progresif yang menghasilkan gambaran makula putih yang tidak bersisik. Mengetahui profil pasien vitiligo di RSUD Dr. Moewardi Surakarta agar tercapai penatalaksanaan yang tepat. Penelitian dilakukan secara retrospektif dengan melihat data rekam medik pasien vitiligo di Poliklinik Dermatologi dan Venereologi RSUD Dr. Moewardi Surakarta periode Januari 2019 - Desember 2022. Pasien vitiligo pada anak dalam kurun waktu 3 tahun didapatkan 42 orang dengan rentang usia terbanyak 13 tahun. Berdasarkan karakteristik jenis kelamin, jumlah pasien vitiligo anak tidak jauh berbeda antara laki-laki dan perempuan, pada laki-laki sebanyak 17 orang (40.48%) dan pada perempuan sebanyak 25 orang (59.52%). Regio lesi terbanyak pada wajah sebanyak 25 orang. Pemberian terapi yang paling banyak diberikan adalah fototerapi dengan distribusi 14 orang (33%) yang menerima terapi ini. 42 pasien vitiligo yang berobat ke Poliklinik Dermatologi dan Venereologi RSUD Dr. Moewardi Surakarta dalam rentang waktu Januari 2019 hingga Desember 2022. Vitiligo pada anak lebih sering terjadi pada wanita dengan kelompok usia terbanyak adalah 13 tahun. Lesi vitiligo yang paling sering muncul di daerah wajah. Terapi terbanyak pada pasien dengan pemberian fototerapi. Kata Kunci: Vitiligo, Fototerapi, Kelainan Pigmentasi